Analisis Hukum dalam Upaya Pencegahan dan Pemberantasan Tindak Pidana Korupsi pada Era Digitalisasi di Bandar Lampung - Sutan Saladin; Juandi Juandi; Zainudin Hasan (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study aims to analyze efforts to prevent and eradicate corruption in the context of digitalization in Bandar Lampung. The digitalization era brings significant changes in the way government and society interact, which has the potential to create opportunities for corrupt practices. The research method used is a qualitative approach with data analysis from interviews, documentation studies, and observations. The results of the study indicate that although there have been preventive measures through the application of information technology, there are still loopholes that can be exploited by perpetrators of corruption. The main causal factors include the lack of legal awareness among the community, as well as minimal supervision and transparency in the use of the budget. This study recommends the need for increased training for law enforcement officers, as well as the implementation of a stricter and more transparent supervision system in the use of digital technology. Thus, this study is expected to provide valuable insights for policy makers in formulating more effective strategies to prevent and eradicate corruption, as well as increasing legal awareness among the Bandar Lampung community in this digital era.